2023
DOI: 10.2903/sp.efsa.2023.en-8015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the factors for the presence of wild boar near outdoor and extensive pig farms in two areas of Eastern Europe

Mario Sebastián‐Pardo,
Eduardo Laguna,
Sándor Csányi
et al.

Abstract: Expanding wild boar populations associate to conflicts with human activities, being a threat to livestock and public health. Particularly, the emergence of African Swine Fever (ASF) in Europe is of major importance. To better understanding the dynamics at the interface between wild boar and domestic pigs in Europe, which is essential to prevent the risk for ASF spread, this report describes (i) the use of extensive pig farm resources by wildlife (wild boar and other mammals) and domestic pigs, and (ii) the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The spatial distribution of the wild boar and domestic pig population densities in all 19 counties in the year of the beginning of the PRRS eradication (2014), in the year of the ASF outbreak (2018), and in the year after the end of the PRRS eradication (2023) shows an overall reduction in the wild boar density and little change in the domestic pig density ( Figure 2 and Figure 3 ). While in 2014 and 2018, the wild boar density per km 2 was 1.13 at the national level, this number decreased to 0.6 wild boar/km 2 by 2023 in the context of the National Action Plan requirements published in 2021 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The spatial distribution of the wild boar and domestic pig population densities in all 19 counties in the year of the beginning of the PRRS eradication (2014), in the year of the ASF outbreak (2018), and in the year after the end of the PRRS eradication (2023) shows an overall reduction in the wild boar density and little change in the domestic pig density ( Figure 2 and Figure 3 ). While in 2014 and 2018, the wild boar density per km 2 was 1.13 at the national level, this number decreased to 0.6 wild boar/km 2 by 2023 in the context of the National Action Plan requirements published in 2021 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study in Serbia reported a frequency of 3.70 weekly visits of wild boars to pig farms, with a higher frequency observed in spring (7.5 visits). Wild boar visits to pig farms were mainly associated with the use of farm resources, such as food and water points [6]. Other studies have found that the proximity of forest to the farm and the distance between pig enclosures and houses (where farmers live) were factors that could influence wild-boar intrusions [7,8], as well as the presence of sows in estrus.…”
Section: Introductionmentioning
confidence: 99%